Modelling sound absorption of tunable double layer woven fabrics. (1st January 2020) - Prasetiyo, Iwan; Muqowi, Eki; Putra, Azma; Novenbrianty, Melissa; Desendra, Gradi; Adhika, Damar Rastri
Abstract: The woven fabric is known to have micro structures inherently so that it can be employed as sound absorber with the same absorption mechanism as the micro-perforated panel (MPP) when it is backed up by an air cavity. In the context of multi-layer system, having high flow resistance at all layers do not guarantee high sound absorption coefficients are achieved apart from narrow absorption bandwidth issue in the MPP. These have been extensively discussed in fibrous porous materials, but it is lacking for the woven fabrics, particularly on the analysis of the relationship of flow resistance for each layer to the sound absorption bandwidth. In this paper, a double-layer system of woven fabric is considered. Two cases are studied: a system with identical flow resistance and one with non-identical flow resistance. The Johnson-Champoux-Allard (JCA) formulation and the transfer matrix method are used to develop the prediction model. It is revealed that for a system with identical flow resistances, high flow resistance produces low amplitude of absorption coefficient, but with relatively wide frequency bandwidth. Lower flow resistance can improve the absorption amplitude, but with a dip in between two absorption peaks which degrades the half absorption bandwidth. This can be solved by having the combination of non-identical resistance between the layers. The selection of flow resistances together with the ratio of the air cavity depths can be used in tuning the performance of the double-layer woven fabric absorber. The experimental data show good agreement with the predictions.